An improved defining parameter for long-period ground motions with application of a super-tall building. Issue 113 (October 2018) - Zhou, Ying; Ping, Tianyao; Gong, Shunming; Zhu, Yi
Abstract: This paper focuses on defining long-period ground motions and analyzing the effect of them on building structures. Increasing attention has been paid to the effect of long-period ground motions on building structures. However, long-period ground motions are not quantitatively defined due to the lack of numerous ground motion investigations. In this paper, based on the statistical analysis of 39, 744 ground motions, an improved frequency-domain defining parameter, namely β l, is firstly proposed to identify long-period ground motions without the necessity of seismological information. Then, based on the definition, long-period ground motions are selected for the time history analysis of a super-tall building structure. The structural responses are obtained under three scenarios: the original ground motion record, the ground motions scaled to minor earthquakes and major earthquakes. To assess the validity of the proposed parameter β l in identifying long-period ground motions, correlation between the structural response and the defining parameter is obtained. Highlights: An improved defining parameter for long-period ground motions is proposed. Characteristics of response spectra for long-period ground motions are analyzed. Responses of a super-tall building under long-period ground motions are analyzed. Relationship between structural responses and ground motion parameter is validated.